Scanning the Future: Veterinary Reproductive Ultrasonography - Mali, A. B.; Mehar, R. M.; Kapane, S. H.; Hadimani, M. R. (Animal Reproduction Update, 2022)
Reproductive ultrasonography can be an extensively preferred diagnostic modality in farm and companion animals for maximizing reproductive health in future days. The shape, contour, size, and position of the structure being analyzed, as well as its echogenicity, which is determined by the amplitude of the echoes received, are being used to describe ultrasound pictures. Reproductive ultrasonography has introduced a new dimension to animal reproduction by allowing not only visualization of the reproductive tract but also early pregnancy diagnosis, surveillance of embryonic or fetus development, and detection of the estrous cycle phase. Confirmation of ovarian and uterine ailments such as cystic ovarian follicle, endometritis, hydrometra, mucometra, and pyometra can be easily diagnosed for the earliest treatment regimens. The technique is a simple, safe, non-invasive, cost-effective, and practical way to confirm reproductive status in farm and companion animals from 30 days of gestation onwards, and by trans-rectal approach, the earliest diagnosis of pregnancy and non-pregnancy in small ruminants and swine can be confirmed from day 20 onwards. As a result, it appears that veterinary reproductive ultrasonography is an excellent technique for managing fertility in farm and companion animals